Human & social impact of technological change in Pakistan: a report on a survey conducted by the University of Dacca and published with the assistance of UNESCO - Husain, A. F. A. (London : Oxford University Press, 1956)
The survey is aimed at making a factual study of the process through which people coming in direct or indirect contact with the new technology are adjusting themselves to the changed environment brought about by it
Includes bibliographical references: v. 1, p. 388-390 and index.
aia 11/07/2017
Loans
Keywords: Social conditions; Industrialization; Technological innovations; Technological innovations--Social aspects; Pakistan